2013
DOI: 10.1186/1471-2407-13-52
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Prognostic Score, an inflammation based prognostic score, predicts survival in patients with hepatocellular carcinoma

Abstract: BackgroundElevated Glasgow Prognostic Score (GPS) has been related to poor prognosis in patients with hepatocellular carcinoma (HCC) undergoing surgical resection or receiving sorafenib. The aim of this study was to investigate the prognostic value of GPS in patients with various stages of the disease and with different liver functional status.MethodsOne hundred and fifty patients with newly diagnosed HCC were prospectively evaluated. Patients were divided according to their GPS scores. Univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 28 publications
4
86
2
1
Order By: Relevance
“…In the same meta-analysis, pooled analysis demonstrated that poor OS and RFS in HCC was significantly associated with CRP ≥10 mg/L, with a HR of 2.15 and 2.66 respectively. Similarly, Kinoshita et al, in two separate studies investigating scoring systems driven by CRP (83,84), again demonstrated the strong correlation between extent and stage of disease and the Glasgow prognostic score (GPS) and CRP/albumin ratio. One hundred and fifty individuals with newly diagnosed HCC at various stages were prospectively followed and divided based on their GPS and modified GPS.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 79%
See 3 more Smart Citations
“…In the same meta-analysis, pooled analysis demonstrated that poor OS and RFS in HCC was significantly associated with CRP ≥10 mg/L, with a HR of 2.15 and 2.66 respectively. Similarly, Kinoshita et al, in two separate studies investigating scoring systems driven by CRP (83,84), again demonstrated the strong correlation between extent and stage of disease and the Glasgow prognostic score (GPS) and CRP/albumin ratio. One hundred and fifty individuals with newly diagnosed HCC at various stages were prospectively followed and divided based on their GPS and modified GPS.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 79%
“…The value of CRP in HCC prognostication has been duplicated and confirmed in various stages of the disease (78,83). It has not only been shown to be predictive of tumor characteristics histologically, but also a useful tool in predicting response to various treatment options and longterm survival afterwards (83,84).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 94%
See 2 more Smart Citations
“…Accumulating evidence indicates the prospective of inflammation-based parameters as prognostic factors (12). This is supported by the wide range of associations between inflammation and tumour initiation, invasion and metastasis (13,14).…”
Section: Introductionmentioning
confidence: 94%